Increasing participation in REDD-plus: a case study from the Nong Bua Lum Phu Province, North-eastern Thailand - Umemiya, Chisa; Wilamart, Suphawadee; Amano, Masahiro (วารสารวนศาสตร์ไทย, 2022)
Lately, under the UN Framework Convention on Climate Change (UNFCCC), there have been discussions on how to incorporate the mitigation efforts of tropical nations in the forestry sector, a process that is known as REDD-plus. As featured at the Fifteenth Conference of Parties (COP15) to the UNFCCC held in 2009, one key element of future REDD-plus is to ensure the broad participation of developing countries. By taking one farmer’s plantation activity in Northeast Thailand that achieved wide participation, this study examined how a diverse range of farmers were able to be involved in the activity. Principal component analysis (PCA) was used to analyze the planters’ motivation. It was found that their motivation varied with their level of income. For wealthy planters, technical kinds of support were particularly motivational; for medium-income and commercial low-income planters, the economic merits of plantations were a key factor; and for poor farmers, a reliable long-term partnership was found to be essential to them. Therefore, it is suggested, for REDD-plus to be widely accepted, various incentives, including non-economic ones, should be prepared so that a wide range of farmers can participate in such a plantation scheme. Further, it is suggested that REDD-plus could effectively promote farmer’s plantation schemes by applying the fund system specifically to enhance a participant’s capacity and capability, and the market mechanism to deliver the economic benefits. Keywords: participation, farmers’ plantations, incentives, REDD-plus, Thailand